The Role of Japan inThe Indonesian Economic - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
ABSTRAK The role of Japan in the demloprrient of the Indonesiurp cor)trornyrs inevitabiy gexting bigger Japan is the bgges1 marker for rndonesiori exports. As it do fn exporis. Japan is also the biggest 562.ffreS of IrnPort. From the bilateral sources of debts, tr Js afaulous thot Japan is a'so frre biggesi sources of loan. In regard of getting the role of Jaxxvi, o ccrioin kinds of atimreness should be !alter} by thf!. ,Ippanese Government to lessen the negairve fee.iing of the society that rptght rise. 10 that which happened in 1974 will newt rake Mace again. keywords: Economic Indonesia